Statues: The Second Book of Foundations - Serres, Michel (Bloomsbury Publishing PLC, 2014)
FC -- Half title -- Also available from Bloomsbury -- Title -- Copyright -- Dedication -- Contents -- STATIONS -- January 28, 1986 At 11:39 And 74 Seconds Later -- THE ROCKET -- First Foundation -- THE SHELL, THE CANNON -- Second Foundation -- Recent Memories -- DRIFTINGS IN THE CEMETERIES -- Space -- Before the War -- FETISHES -- Time -- Around 1900 -- THE GATES OF HELL -- Mass -- THE EIFFEL TOWER -- Work -- 1883â1884 -- THREE TALES BY MAUPASSANT -- THE TIC -- The Senses -- THE HAIR -- Object, Dead Body -- BESIDE A DEAD MAN -- Dentures, Movement -- During the Grand SiÃ¨cle -- THE BEAM -- Object, God -- COSTUMES -- Solid -- Quattrocento -- THE HAMMER -- Homo Faber -- About the Year 33 of our Era -- MAGDALENE AND LAZARUS -- Knowledge -- Zero -- RAPTURE -- Weight -- Fifth Century before Christ -- EMPEDOCLESâS RETURN -- Fire -- Four Millennia Ago -- THE SECRET OF THE SPHINX -- Substitution -- Undated -- THE MYTH OF SISYPHUS -- Falling Bodies -- ORPHEUS, LOTâS WIFE -- Sculpture, Music -- THE STATUE OF HESTIA -- Epistemology -- Notes